Паралельні імунні системи для розпізнавання образів - Дараган, Д. М. (ХНУРЕ, 2024)
The subject of the proposed paper is the use of parallel distributed computing on GPUs to solve the problem of pattern recognition by means of artificial immune systems. The purpose of this work is to review the prospects for the use of modern hardware for the study of areas of artificial intelligence, inhibited by the level of technical development. The relevance of the work lies in the constant growth of data volumes and the need for their processing using advanced methods. The theoretical foundations of the subject were considered, assumptions were made regarding the effectiveness of an approach, and prospects for future research were outlined.
Keywords: паралельна імунна система; розпізнавання образів